Open data: Emotional Responses in Spider Fear Are Closely Related to Picture Awarenes - Stefan Wiens (Stockholm University, 2019)
The files are in reference to this paper:

Peira, Nathalie, Armita Golkar, Arne Öhman, Silke Anders, and Stefan Wiens. Emotional Responses in Spider Fear Are Closely Related to Picture Awareness. Cognition & Emotion 26, no. 2 (February 2012): 252–60. https://doi.org/10.1080/02699931.2011.579087.

Note that the actual number of subjects was 37 (20 fearful), not 36 (as stated in the paper).

The "Peira2012Rawdata.xls" contains the raw data (as Excelfile; https://microsoft-excel.en.softonic.com/). The same data are also saved as separate tab-separated textfiles. Thus, the Excelfile is not necessary but provided for convenience.

The main tabs/files are:
_General_:
Id
FearGr 0=no spider fear, 1=spider fear
fear=([1,3,4,7,8,9,10,12,13,20,21,22,24,25,28,30,31,32,34,36]);
nofear=([2,5,6,11,14,15,16,17,18,19,23,26,27,29,33,35,37]);
spweb modified SAS questionnaire before participation
SPQ spider fear questionnaire
STAI trait anxiety
DS disgust sensitivity

_Detect_: mean recognition ratings
_Rate_: mean emotion ratings
_SCLmean_: mean skin conductance levels for the three tasks (view, detect, rate)
_HRmean_: mean heart rates for the three tasks (view, detect, rate)

The variable names are:
f20 f40 f70 f200
s20 s40 s70 s200
Note that f refers to flower and s to spider. 20,40,70, and 200 refer to different SOAs (stimulus onset asynchronies).

The files in the Peira2012SPSS.zip are not necessary. They just illustrate how we conducted some of the analyses in SPSS (https://www.ibm.com/products/spss-statistics).
Keywords: 170101 Biological Psychology (Neuropsychology, Psychopharmacology, Physiological Psychology); Neuroscience and Physiological Psychology; Neurosciences; Neurovetenskaper; Biological Sciences; Biologi